Establishing Logistics Service Strategies That Increase Sales. Issue 3 (23rd August 2016) - Leuschner, Rudolf; Lambert, Douglas M.
Abstract : While the linkage between logistics performance and firm performance has received attention in the literature, typically firm performance is measured as customer satisfaction and customer loyalty rather than share of business or other measures that translate into a financial benefit. Thus logistics executives continue to be judged primarily on cost and asset reductions. Only one study has documented how logistics performance affects customer satisfaction and the percentage of business allocated to the suppliers as well as the differences in outcomes between firms identified as primary and secondary suppliers (Leuschner et al.2012 ). In this research, we use samples in the motion picture and video production industry, and the plastic materials and resins industry to investigate the impact of the Marketing Mix on customer satisfaction and share of business. Our results differ from Leuschner et al. (2012 ) regarding the impact of product, price, and promotion on customer satisfaction, but we confirm the impact of logistics performance on customer satisfaction and the relationship between customer satisfaction and share of business for primary and secondary suppliers combined. Finally, we provide a framework to identify logistics service strategies based on a customer's current profitability, potential growth, and the share of a customer's purchases obtained.